Food system transformation: a progressive place-based approach. Issue 7 (3rd July 2022) - Sonnino, Roberta; Milbourne, Paul
ABSTRACT: Responding to growing calls for research that engages with the complexity of food system transformation, in this paper we focus on place as an "active meso-level mediator" between the multiple tensions and contestations that surround processes of change. Drawing on Massey's notion of a "progressive sense of place", we identify, through a critical review of the literature, four main features of this concept that, taken together, have a unique contribution to make to ongoing efforts to conceptualise and tackle the interwoven socio-ecological issues that affect the food system, and to position justice at the centre of its transformation. These include: (i) the socio-natural composition of place; (ii) the positive interactions and connections that underpin spatial identity; (iii) the social processes (including power dynamics) that shape everyday spatial practices; and (iv) the flows of ideas, materials, people and resources that cut across space. With special attention given to their interdependence and their implications for the functioning of food systems, these four features provide the basis for the development of an innovative and socio-spatially inclusive place-based framework for food system transformation that integrates ideas of sustainability co-benefits, spatial linkages, social inclusion and sectoral connectivities. This framework, we argue, provides a broader and more critical academic understanding of food system transformation at both the macro- and the micro-levels. It also enables the formulation of legislative frameworks, policies and practices to deliver such transformation.